2014
DOI: 10.1371/journal.pone.0110269
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Risks Associated with Low Dose Ionizing Particle Radiation

Abstract: Previous epidemiologic data demonstrate that cardiovascular (CV) morbidity and mortality may occur decades after ionizing radiation exposure. With increased use of proton and carbon ion radiotherapy and concerns about space radiation exposures to astronauts on future long-duration exploration-type missions, the long-term effects and risks of low-dose charged particle irradiation on the CV system must be better appreciated. Here we report on the long-term effects of whole-body proton (1H; 0.5 Gy, 1 GeV) and iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 33 publications
3
66
0
1
Order By: Relevance
“…Due to experimental set-up and limited availability of tissues, we did not have the opportunity to include other time points or assess cardiac function or histology. However, previous research in a similar mouse model of exposure to protons (0.5 Gy, 1 GeV) and 56 Fe (0.15 Gy, 1 GeV/n) showed long-term alterations in cardiac function and structure in response to these charged particles [13-15]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to experimental set-up and limited availability of tissues, we did not have the opportunity to include other time points or assess cardiac function or histology. However, previous research in a similar mouse model of exposure to protons (0.5 Gy, 1 GeV) and 56 Fe (0.15 Gy, 1 GeV/n) showed long-term alterations in cardiac function and structure in response to these charged particles [13-15]. …”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, recent work on tissue samples of lung [34] and brain (Antiño Allen, PhD, personal communication) of mouse models showed that protons followed at 24 hours by 56 Fe resulted in molecular and functional alterations that were significantly different when compared to either source of radiation alone. Moreover, in mice that were challenged with an acute myocardial infarction, prior proton irradiation increased the expression of pro-survival genes, improved the restoration of cardiac function, and enhanced the process of cardiac remodeling when examined from hours to months after irradiation [13]. Our work confirms these earlier findings and demonstrates that the molecular and cellular response of the heart can be modified by a priming dose of protons at lower energy levels (150 MeV) than in the previous report by Yan et al (1 GeV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to high doses of radiation, low-dose ionizing radiation (LDIR) might increase the risk of cardiovascular disease, lens opacity, and some other noncancerous diseases (Hammer et al, 2013;Kamiya et al, 2015;Kreuzer et al, 2015). The authors of previous research have reported that cardiovascular morbidity and mortality may occur decades after ionizing radiation exposure (Yan et al, 2014). The health risks arising from exposure to low doses of ionizing radiation should be re-evaluated (El-Saghire et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary concerns for space travel is exposure to space radiation. Radiation exposure and more significantly space radiation have been connected with increased carcinogenesis, cataract development, neurological health risks of the central nervous system and cardiovascular disease, as well as with short-term adverse effects that could compromise mission success (16). Radiation can also leads to perturbations of metabolic processes and inflammatory processes, and these changes can be reflected in biofluids, such as urine and blood, that could provide a snap shot of an individual’s current physiological state.…”
Section: Introductionmentioning
confidence: 99%